Exploring the Experience of Start-ups in Open Innovation Programs in Portugal: An Analysis of Perceptions and Positive Impacts - Claudio Ferreira Bueno Neto (2023)
Open innovation has become a popular approach for innovation all over the world, including in Portugal. This study explores the experience of start-ups in Open Innovation programs from Portugal, analysing their perception and positive impacts of adopting this approach. A qualitative research method was used to achieve this goal based on in-depth interviews with four start-up entrepreneurs who have engaged in open innovation practices and 1 of the companies responsible for these open innovation programs. The interviews were analysed using thematic analysis, which revealed several prominent themes. The positive perceptions identified are (i) the significance of validation and reputation for start-ups when collaborating with larger companies; (ii) the advantages of gaining a better understanding of corporate procedures, particularly for those who lacked prior experience working with larger companies; (iii) the impact of open innovation programs on business scaling and revenue generation; (iv) the monetary prize offered by such programs was seen as crucial for establishing long-term strategies; (v) accessing the perspectives of industry experts was also identified as a valuable advantage, which validate the previous studies on the topic. The findings of this study provide insights into the open innovation experience of start-ups and underscore the significant role that large companies play as validators and facilitators of further opportunities. The start-up feedback highlights the value of working with established companies to validate their solutions and access new projects. Further research could build upon these findings to examine the open innovation experience of start-ups in other countries and to identify best practices that can be applied to support start-ups in their open innovation journey. The findings of this study could have implications for policymakers and practitioners interested in promoting innovation ecosystems, particularly those focused on start-up development and entrepreneurship. In conclusion, this study sheds light on the experience of start-ups participating in Portuguese open innovation programs and highlights some of the positive and negative impacts they gain from adopting this approach. Future research could also explore how established companies can learn from the open innovation practices from the start-ups' point of view and how they can create a culture that supports innovation, fosters collaboration with external partners, and encourages adopting open innovation practices.